Loneliness and social isolation in old age correlates and implications - Hajek, André 1983-; Riedel-Heller, Steffi Gerlinde 1964-; König, Hans-Helmut 1965- (Routledge, 2023)
This book is a seminal guide to loneliness and social isolation in old age, providing a comprehensive overview of the important correlates of socioeconomic, health and lifestyle factors upon loneliness and social isolation in old age. Bringing together contributions from leading authorities, the book showcases expertise from, among other things, medicine, psychology, epidemiology, sociology, economics and gerontology. It shows the importance of identifying factors associated with loneliness and social isolation among older adults from a broader perspective, and includes discussion of a range of topics including income poverty, physical activity, family care and frailty. The chapters are evidence-based and offer a mix of empirical studies as well as reviews of international research. The book also discusses policy implications and provides an overview of nationally representative cohort studies around the world available to researchers quantifying loneliness or social isolation. This book is unique in examining loneliness and social isolation from such wide-ranging perspectives and will be essential reading for researchers and postgraduate students in the areas of e.g., mental health research, social work, and psychiatry. Health professionals involved with gerontology and geriatrics will also find this book of benefit.